2018
DOI: 10.1002/1878-0261.12201
|View full text |Cite|
|
Sign up to set email alerts
|

Microfluidic enrichment of plasma cells improves treatment of multiple myeloma

Abstract: Cytogenetic alterations form the basis for risk stratification for multiple myeloma (MM) and guide the selection of therapy; however, current pathology assays performed on bone marrow samples can produce false‐negatives due to the unpredictable distribution and rarity of MM cells. Here, we report on a microfluidic device used to facilitate CD45 depletion to enhance the detection of cytogenetic alterations in plasma cells (PCs). Bone marrow samples from 48 patients with MM were each divided into two aliquots. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The inconsistency may be derived from inter-tumor and intra-tumor heterogeneity as these results were based on assays on bulky tumors. We have recently shown that a cancer relapse signaling pathway can be detected only in a single-cell transcriptome, not in a bulky tumor analysis, as bulky tumor transcriptomic analyses obscure the low signal of certain biomarkers [ 8 ]. We rationalized that single-cell transcriptomic analysis can enhance signal-to-noise ratio over bulky tumor transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency may be derived from inter-tumor and intra-tumor heterogeneity as these results were based on assays on bulky tumors. We have recently shown that a cancer relapse signaling pathway can be detected only in a single-cell transcriptome, not in a bulky tumor analysis, as bulky tumor transcriptomic analyses obscure the low signal of certain biomarkers [ 8 ]. We rationalized that single-cell transcriptomic analysis can enhance signal-to-noise ratio over bulky tumor transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While single-cell proteomics is still uncertain, single-cell RNA-seq is a widespread practice in research laboratories now. Many microfluidic devices, including ours, have been developed for single-cell transcriptome analysis[ 17 ] but clinical application of single-cell transcriptome is still not common, especially in cancer characterization and classification. US Food and Drug Administration approved CellSearch™ (Janssen, Raritan, NJ) of circulating tumor cells (CTC) for predicting PFS and OS in metastatic breast cancer for clinical use in 2005.…”
Section: Development Of An Innovative Single-cell Molecular Profilingmentioning
confidence: 99%
“…We have conducted and published a small Phase I clinical trial with our devices in myeloma risk stratification of MM[ 26 ]. As a proof-of-concept for instrumentation of our prototype device, we published the clinical trial using MLSCA/MF-CD45-TACs on MM 48 patients[ 17 ], which shed new light for scale-up applications in clinics.…”
Section: Development Of An Innovative Single-cell Molecular Profilingmentioning
confidence: 99%
See 2 more Smart Citations